(untitled) (Progressive Agriculture, 2014)
Seed health of aromatic rice variety Kalijira collected from Mymensingh Sadar Upazilla was studied following standard blotter method. Six different treatments namely water wash, garlic (1 : 1), water wash + garlic (1 : 1), Knowin 50WP (Carbendazim) @ 0.2% and water wash + Knowin-50WP @ 0.2% were used in this experiment. The identified seed-borne fungi were Alternaria padwickii, Aspergillus niger, Aspergillus flavus, Bipolaris oryzae, Curvularia lunata, Fusarium moniliforme, Fusarium oxysporum and Penicillium sp. Highest seed infection (30.67%) was recorded for F. oxysporum and the lowest seed infection (9.33%) was recorded for A. padwickii. Germination of seeds significantly varied in different treatments that ranged from 85.33 to 98.86%. Among the treatments, the highest (98.86%) germination was found by water wash + Knowin-50WP and lowest (85.33%) by control (untreated). After washing of seeds in water, the treated seeds with plant extract or chemical showing better performance than when only treated with plant extract or chemical for controlling seed borne pathogens. DOI: http://dx.doi.org/10.3329/pa.v24i1-2.19098 Progress. Agric. 24(1&2): 45 - 51, 2013